A digestion method and determination method for accurate analysis of trace element content of alumina fiber
Patent Information
- Application Number
- CN202211336329.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-28
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2042-10-28
AI Technical Summary
[0004]鉴于上述的分析,本发明实施例旨在提供一种氧化铝纤维微量元素含量准确分析的消解方法及测定方法,用以解决现有氧化铝消解和测定方法至少以下问题之一:1、因氧化铝纤维消解需要耐强酸和高温,消解过程中需一直采用铂金坩埚,成本高;2、加入的硫酸沸点高,赶酸的耗时长,测定效率大大降低;3、无法保证最终测定体系内没有硫酸等试剂残留,残留的硫酸等试剂会导致谱峰干扰,影响测定准确性;4、测定时间长,加热赶酸等过程需敞口,样品长时间暴露在空气中可能会引入杂质影响测定结果准确性
[0028]与现有技术相比,本发明至少可实现如下有益效果之一:
Smart Images

Figure CN117949438B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of chemical technology, and in particular to a digestion method and determination method for accurate analysis of trace element content in alumina fibers. Background Technology
[0002] Oxide fiber reinforced oxide ceramic matrix composites are a class of materials that use oxide ceramics as the matrix and combine them with oxide fibers. They possess characteristics such as low density, high temperature resistance, thermal shock resistance, and oxidation resistance, making them ideal candidate materials for applications in high-temperature, oxygen-rich environments. They have enormous application potential in aerospace hot-end components and are currently used in various weapon systems. The reinforcing fibers primarily utilize Al2O3 fibers or Al2O3-SiO2 ceramic fibers, which exhibit high tensile strength and modulus, and excellent high-temperature oxidation resistance. The excellent performance of alumina fibers is closely related to their internal structure and the content of various elements. The content of impurity elements in alumina fibers, such as Na, K, Mg, Fe, and Ca, significantly affects the fiber's performance. For example, Na2O affects the phase transformation of α-Al2O3. When calcined at high temperatures, Na2O reacts with Al2O3 to form sodium peraluminate, which is structurally stable at high temperatures and coexists with α-Al2O3. During calcination, Na2O significantly reduces the conversion rate and efficiency of α-Al2O3, while also coarsening the alumina grains, reducing the specific surface area, and causing irregular crystal morphology. Meanwhile, the presence of sodium affects the dielectric properties of the fiber; the higher the sodium content, the worse the insulation of the fiber. Similarly, the presence of Fe₂O₃ lowers the sintering temperature, affecting the material's electrical breakdown strength and flexural strength. Ca and Mg form calcium hexaaluminate and spinel during ceramic formation, reducing the main crystalline phase of alumina. The presence of these trace elements has a dramatically increased impact on material properties under high-temperature operating conditions. Therefore, accurately measuring the trace element content in alumina fibers is crucial for the quality control of alumina fibers, and the accurate determination of trace elements in alumina fibers depends on the completeness of the alumina fiber digestion process.
[0003] Existing methods for digesting and determining alumina fibers cannot guarantee the accurate analysis of trace elements in these fibers, thus compromising fiber quality, raw material selection, and the performance of fiber-reinforced ceramic matrix composites. Therefore, there is an urgent need to develop digestion and determination methods suitable for both digesting alumina fiber samples and accurately analyzing their trace elements. This will ensure the reliability of trace element analysis results and promote in-depth research and application of alumina fibers. Summary of the Invention
[0004] Based on the above analysis, the embodiments of the present invention aim to provide a digestion and determination method for accurate analysis of trace element content in alumina fibers, in order to solve at least one of the following problems in existing alumina digestion and determination methods: 1. Because alumina fiber digestion requires resistance to strong acids and high temperatures, a platinum crucible must be used throughout the digestion process, resulting in high costs; 2. The added sulfuric acid has a high boiling point, and the acid removal process is time-consuming, greatly reducing the determination efficiency; 3. It is impossible to guarantee that there are no residual sulfuric acid or other reagents in the final determination system, and the residual sulfuric acid or other reagents will cause spectral peak interference, affecting the accuracy of the determination; 4. The determination time is long, and the heating and acid removal processes require an open environment, and the long-term exposure of the sample to air may introduce impurities that affect the accuracy of the determination results.
[0005] The main objective of this invention is achieved through the following technical solution:
[0006] This invention provides a digestion method for accurate analysis of trace element content in alumina fibers, comprising the following steps:
[0007] Step 1: Place the alumina fiber sample into a platinum crucible, place it in a muffle furnace, and heat it;
[0008] Step 2: Remove the alumina fiber sample and place it in a desiccator to cool to room temperature for later use;
[0009] Step 3: Weigh a certain amount of alumina fiber sample, put it into a centrifuge tube, moisten it with a small amount of water, add HCl, HNO3 and HF to the centrifuge tube, seal and shake well, place the centrifuge tube on a graphite digestion furnace and heat at low temperature until the fiber dissolves.
[0010] Step 4: After the centrifuge tube has cooled to room temperature, unscrew the cap of the centrifuge tube and evaporate it in the open on the graphite digestion furnace until all the liquid has evaporated. Remove the centrifuge tube and let it cool slightly. Add HNO3 and continue to evaporate it in the open on the graphite digestion furnace until all the liquid has evaporated.
[0011] Step 5: Remove the centrifuge tube and let it cool slightly. Rinse the inner wall of the centrifuge tube with a small amount of water, add HNO3 and water, seal and shake well. Place the centrifuge tube on a graphite digestion furnace and heat at a low temperature until the salts are completely dissolved.
[0012] Step 6: Remove the centrifuge tube and cool it to room temperature. Transfer all the liquid to a volumetric flask, rinse the inner wall of the tube with water, and transfer all the rinsing liquid to the volumetric flask as well. Make up to volume and shake well. Analyze the elements in the sample using ICP-OES.
[0013] Furthermore, in step 1, the heating temperature is 620–680°C, and the heating time is 1–2 hours.
[0014] Furthermore, in step 3, the centrifuge tubes are placed on a graphite digestion furnace and heated at a low temperature of 110–130°C for 1–3 hours.
[0015] Furthermore, in step 4, the centrifuge tube cap is unscrewed, and the tube is opened and evaporated in a graphite digestion furnace at an open temperature of 110–130°C for 5–7 hours.
[0016] Further, in step 5, the centrifuge tube is removed and cooled slightly to 40-60°C. After rinsing the inner wall of the centrifuge tube with a small amount of water, 2-4 mL of HNO3 and 10-15 mL of water are added. The centrifuge tube is then placed on a graphite digestion furnace and heated at 110-130°C for 1.5-2.5 hours.
[0017] Furthermore, in step 3, the mass-to-volume ratio of the alumina fiber sample, HCl, HNO3, and HF is 0.4–0.5 g: 3–4 mL: 3–4 mL: 6–8 mL;
[0018] Preferably, the alumina fiber sample has a mass of 0.4–0.5 g, the HCl volume is 3–4 mL, the HNO3 volume is 3–4 mL, and the HF volume is 6–8 mL.
[0019] Furthermore, in step 6, the sample in the centrifuge tube is transferred to a 25 mL volumetric flask, brought to a final volume, and shaken well. ICP-OES is then used to analyze five elements in the sample: Na, K, Mg, Fe, and Ca. The relative standard deviation of the measurement results is <2.5%.
[0020] Furthermore, in step 3, the aperture of the graphite digestion furnace and the diameter of the centrifuge tube are the same.
[0021] Furthermore, in step 4, the centrifuge tube is removed and cooled slightly to 40-60°C, 1-2 mL of HNO3 is added, and the mixture is then evaporated in an open container at 110-130°C in a graphite digestion furnace until all the liquid has evaporated.
[0022] This invention also provides a method for accurately analyzing the trace element content of alumina fibers, wherein the digestion method is used to digest the alumina fiber sample, and the method includes the following steps:
[0023] S1. The alumina fiber sample is digested by the digestion method described above. After digestion, the sample is transferred to a volumetric flask, diluted and shaken to obtain the stock solution for testing.
[0024] S2. Prepare a blank sample solution according to the digestion method described above;
[0025] S3. Prepare a series of standard solutions;
[0026] S4. Use ICP-OES to measure the spectral intensity of each element in sequence, select appropriate characteristic spectral lines, and establish a standard working curve;
[0027] S5. Use ICP-OES to determine the spectral intensity of relevant elements in the sample solution, and calculate the content of relevant elements in the sample according to the standard working curve.
[0028] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:
[0029] 1. This invention designs a digestion method for alumina fibers, which can be applied to the digestion of alumina fibers with different ratios and has a certain degree of versatility.
[0030] 2. The technical route of the present invention does not require the addition of H2SO4, which can reduce the high-temperature heating (the boiling point of concentrated sulfuric acid is 337°C) and digestion time required for the removal of H2SO4.
[0031] 3. In this invention, the acidic reagent is evaporated to dryness, and HNO3 is repeatedly added and evaporated to dryness again. By using a multiple acid removal method, excess HCl and HF during the digestion process are removed, which greatly reduces spectral peak interference and damage to the equipment in ICP-OES analysis, and improves the repeatability and accuracy of the measurement results.
[0032] 4. The final analytical solution of this invention is an HNO3 matrix environment with a mass fraction of approximately 5%, which is beneficial for accurate analysis of trace elements and reduces errors. This invention determines an appropriate sample volume, ensuring complete sample digestion to meet the sample amounts required for various trace element determinations, avoiding the influence of incomplete sample dissolution on the trace element content determination results. This invention uses the standard addition method to control the dilution factor, reducing errors in trace element determination caused by excessive dilution.
[0033] In this invention, the above-described technical solutions can be combined with each other to achieve more preferred combinations. Other features and advantages of this invention will be set forth in the following description, and some advantages may become apparent from the description or be learned by practicing the invention. The objects and other advantages of this invention can be realized and obtained from what is particularly pointed out in the description and drawings. Attached Figure Description
[0034] The accompanying drawings are for illustrative purposes only and are not intended to limit the invention. Throughout the drawings, the same reference numerals denote the same parts.
[0035] Figure 1 This is a comparison chart of the trace element content determination values of Example 2 and Comparative Example 1 of the present invention;
[0036] Figure 2 The RSD values for trace element determination are shown in Example 2 and Comparative Example 1 of this invention. Detailed Implementation
[0037] Preferred embodiments of the present invention will now be described in detail with reference to the accompanying drawings, which form part of this application and are used together with the embodiments of the present invention to illustrate the principles of the present invention, but are not intended to limit the scope of the present invention.
[0038] A digestion method for accurate analysis of trace element content in alumina fibers, comprising the following steps:
[0039] 1. Place the alumina fiber sample in a platinum crucible, put it in a muffle furnace, and heat it;
[0040] 2. Remove the alumina fiber sample and place it in a desiccator to cool to room temperature for later use;
[0041] 3. Weigh a certain amount of alumina fiber sample, put it into a centrifuge tube, moisten it with a small amount of water, add HCl, HNO3 and HF to the centrifuge tube, seal and shake well, place the centrifuge tube on a graphite digestion furnace and heat at low temperature until the fiber dissolves.
[0042] 4. After the centrifuge tube has cooled to room temperature, unscrew the cap of the centrifuge tube and evaporate it in the open on the graphite digestion furnace until all the liquid has evaporated. Remove the centrifuge tube and let it cool slightly. Add HNO3 and continue to evaporate it in the open on the graphite digestion furnace until all the liquid has evaporated.
[0043] 5. Remove the centrifuge tube and let it cool slightly. Rinse the inner wall of the centrifuge tube with a small amount of water, add HNO3 and water, seal and shake well. Place the centrifuge tube on a graphite digestion furnace and heat at a low temperature until the salts are completely dissolved.
[0044] 6. Remove the centrifuge tube and cool it to room temperature. Transfer all the liquid to a volumetric flask, rinse the inner wall of the tube with water, and transfer all the rinsing liquid to the volumetric flask as well. Make up to volume and shake well. Then, analyze the elements in the sample using ICP-OES.
[0045] Alumina fiber is one of the newest ultralight high-temperature insulation materials both domestically and internationally. It utilizes a high-tech sol-gel method, where soluble aluminum and silicon salts are formulated into a colloidal solution with a certain viscosity. This solution is then centrifuged at high speed to form fiber preforms, which are subsequently dehydrated, dried, and subjected to medium-to-high temperature heat treatment for crystallization, transforming them into alumina fibers. Existing alumina digestion methods primarily involve adding sulfuric acid and hydrofluoric acid to a platinum crucible and heating to dissolve and remove the sulfuric acid. However, these methods suffer from drawbacks such as long measurement times, low efficiency, high cost, and the inability to guarantee the absence of residual sulfuric acid and other reagents in the final measurement system, which can cause spectral interference. Furthermore, the long measurement time and the need for open heating processes to remove acid can introduce impurities that may affect the accuracy of the results. The digestion method of this invention does not require the addition of H2SO4, which reduces the high-temperature heating and digestion time required to remove H2SO4. The fiber sample is digested by adding a certain proportion of acid washing reagents HCl, HNO3 and HF, and the acidic reagents, especially HCl and HF, are removed by multiple acid removal processes. This avoids interference with ICP-OES analysis and damage to the equipment, and improves the repeatability and accuracy of the measurement results.
[0046] Specifically, in step 1, the alumina fiber sample can be long alumina fibers, short alumina fibers, or alumina whiskers. Typically, continuous long alumina fibers are used to reinforce oxide ceramic matrix composites. The alumina fibers used in this embodiment are long alumina fibers with an Al:Si ratio of 72:28 or 80:28, and fiber diameters are all around 10 μm. When determining trace elements, to increase the solubility of the alumina fibers and reduce the dissolution time, the long alumina fibers need to be cut into short fibers with a length of less than 10 mm. To avoid lint or adhesion to the centrifuge tubes during transfer, this process usually occurs after heating the fiber sample to remove the surface wetting agent or adhesive. Depending on the tolerance of the selected alumina fiber sample surface wetting agent or adhesive, the heating temperature is 620–680 °C, and the heating time is 1–2 h. Within this heating temperature range, the surface wetting agent or adhesive of the alumina fiber sample can decompose. The heating time of 1–2 h ensures complete removal of the wetting agent or adhesive from the alumina surface. The mass of the alumina fiber sample is 4-5g.
[0047] Specifically, in step 2, the sample is placed in a clean bottle to prevent the fiber from being contaminated, which would affect the determination of trace element content.
[0048] Specifically, in step 3, the mass-to-volume ratio of alumina fiber sample, HCl, HNO3, and HF is 0.4–0.5 g : 3–4 mL : 3–4 mL : 6–8 mL. Preferably, the mass of the alumina fiber sample is 0.4–0.5 g, the volume of HCl is 3–4 mL, the volume of HNO3 is 3–4 mL, and the volume of HF is 6–8 mL. For example, 0.4 g of alumina fiber sample, 4 mL of HCl, 4 mL of HNO3, and 8 mL of HF are added to a centrifuge tube, or 0.5 g of alumina fiber sample, 3 mL of HCl, 3 mL of HNO3, and 6 mL of HF are added. A mass of 0.4–0.5 g of alumina fiber sample saves on acid reagents while ensuring complete dissolution of the alumina fiber sample. Too much acid can dissolve the fiber sample completely but will lead to excessively long acid removal time and reduced measurement efficiency; too little acid will prevent the fiber sample from dissolving completely. The added acid reagents are directly purchased analytical grade concentrated hydrochloric acid (36%–38% by mass), concentrated nitric acid (65%–68% by mass), and concentrated HF (50% by mass). HF is added to break the silicon-oxygen bonds in the fiber sample, forming volatile SiF4, thereby removing Si. HNO3 and HCl are added to react with the metal compounds in the fiber sample, converting the metal elements into soluble salts. Sealing and shaking ensures sufficient reaction between the acid reagents and the sample. The appropriate amounts of HCl, HNO3, and HF added prevent excessive pressure buildup in the sealed centrifuge tubes, which could lead to an explosion. The centrifuge tubes are placed in a graphite digestion furnace and heated at a low temperature of 110–130°C for 1–3 hours. Within this temperature range, the various acid reagents exhibit maximum activity, making it most suitable for dissolving the fiber sample. Furthermore, within the high-temperature range that the centrifuge tubes can withstand, a heating time of 1–3 hours ensures complete dissolution of the alumina fibers. Preferably, the centrifuge tube volume is 50 mL.
[0049] Specifically, in step 4, cooling the centrifuge tube to room temperature is to prevent the test solution from splashing when the sealed heating centrifuge tube is opened at high temperature due to pressure inside. The evaporation temperature is set according to the boiling points of the acidic reagents (hydrofluoric acid 105℃, nitric acid 83℃). The sample liquid in the centrifuge tube is evaporated in an open environment on a graphite digestion furnace at 110–130℃ for 5–7 hours to ensure complete evaporation. The centrifuge tube is then removed and cooled slightly to 40–60℃ to prevent splashing when adding liquid directly at high temperature. 1–2 mL of HNO3 is added, and the tube is continued to be heated in an open environment on the graphite digestion furnace until all liquid has evaporated. This open-environment heating and evaporation is to remove the acid added in step 3. The addition of HNO3 again ensures the removal of excess HCl and HF. Removing residual HF prevents corrosion of the ICP-OES nebulizer and rectangular tube, and removing residual HCl avoids interference signals from Cl-, thus improving the accuracy of the measurement results. The step of adding 1-2 mL of HNO3 can be repeated, and the liquid can be heated again until it has completely evaporated to ensure that HCl and HF are completely removed and reduce their impact on the measurement results.
[0050] Specifically, in step 5, remove the centrifuge tube and cool it slightly to 40–60°C. Rinse the inner wall of the centrifuge tube with a small amount of water, then add 2–4 mL of HNO3 and 10–15 mL of water to provide a dilute nitric acid dissolution environment for the fiber sample to be tested. The measurement effect is best in a dilute acid environment, which can eliminate interference from impurity ions. Metal ions are more stable in a nitric acid environment, which helps improve the repeatability of ICP-OES measurement results. Seal and shake well, then place the centrifuge tube on a graphite digestion furnace and heat at 110–130°C for 1.5–2.5 hours. This temperature range is within the high-temperature range that the centrifuge tube can withstand; the higher the temperature, the better it is for dissolving salt samples. Heating for 1.5–2.5 hours ensures complete dissolution of the metal salts. This step is to allow the metal salts to redissolve; sealing improves dissolution efficiency while preventing the loss of volatile elements.
[0051] Specifically, in step 6, the pipette is used to transfer all the liquid to a 25mL volumetric flask, the inner wall of the tube is rinsed with water, and the rinsing liquid is also transferred to the volumetric flask using a pipette. Then, the volume is adjusted and the solution is shaken well to prepare the stock solution for later use.
[0052] Specifically, the graphite digestion furnace used in this invention has the same aperture as the centrifuge tube diameter, which can increase the heating area of the centrifuge tube and ensure uniform heating of the centrifuge tube.
[0053] Specifically, through steps 1-6, the stock solution for the alumina fiber sample to be tested is obtained. A working curve is plotted using inductively coupled plasma optical emission spectrometry (ICP-OES) to measure the standard solution. The sample to be tested is then measured, and the contents of trace elements such as Na, K, Mg, Fe, and Ca in the alumina fiber sample are calculated based on the working curve. It should be noted that because the digested sample is a high-alumina sample, the standard addition method is used for determination to eliminate the influence of the aluminum matrix effect on the measurement results. Preferably, for unknown samples, the external standard method can be performed first to obtain the approximate concentration of each element, and then the standard solution preparation scheme for the standard addition method can be calculated accordingly.
[0054] Specifically, this invention provides a method for accurately analyzing the trace element content of alumina fibers, comprising the following steps:
[0055] S1. The alumina fiber sample is digested using the digestion method of the present invention. After digestion, the sample is transferred to a volumetric flask, diluted, and shaken to obtain a stock solution for testing.
[0056] S2. Prepare a blank sample solution according to the digestion method of the present invention for later use;
[0057] S3. Prepare a series of standard solutions;
[0058] S4. Use ICP-OES to measure the spectral intensity of each element in sequence, select appropriate characteristic spectral lines, and establish a standard working curve;
[0059] S5. Use ICP-OES to determine the spectral intensity of relevant elements in the sample solution, and calculate the content of relevant elements in the sample according to the standard working curve.
[0060] Specifically, in step S1, based on the trace element content of the fiber sample to be tested and the concentration requirements for trace element determination by ICP-OES, the test mother liquor is diluted again by a certain factor until the concentration requirements for trace element determination by ICP-OES are met.
[0061] Specifically, in step S3, a series of standard solutions are prepared according to the trace element content range of the fiber sample to be tested. The preparation process of the series of standard solutions includes:
[0062] S301: Dilute the multi-element national standard solution;
[0063] S302: Take a certain amount of the test stock solution and a certain amount of the diluted multi-element national standard solution, dilute again, and make up to volume to obtain a series of standard solutions. The content of the analyte in the series of standard solutions forms a gradient from low to high, and the linear range includes the content of the analyte.
[0064] Specifically, in S4, the spectral intensity of each element is measured sequentially using ICP-OES to obtain a working curve of signal intensity versus element concentration. The horizontal axis represents the concentration (mg / L) of the series of standard solutions for each metal element, and the vertical axis represents the emission intensity of each element at different concentrations using plasma emission spectra. The control software automatically performs univariate linear regression analysis to establish the working curve. The linear correlation coefficient γ of the working curve should not be less than 0.999; otherwise, the cause should be identified and eliminated before a new calibration curve is established.
[0065] The following examples illustrate a digestion method provided by the present invention suitable for accurate analysis of trace element content in alumina fibers.
[0066] Example 1
[0067] The digestion method of this invention was used to completely digest a certain type of imported alumina fiber (main element Al:Si ratio 72:28) for trace element detection. This experiment measured 5 parallel samples and 1 blank sample. The specific steps are as follows:
[0068] 1. Take 5g of fiber sample and place it in a platinum crucible. Place it in a muffle furnace and heat at 625℃ for 2 hours to completely remove the sizing agent or adhesive from the fiber surface.
[0069] 2. Remove the sample and place it in a desiccator to cool to room temperature. Cut it into short fibers with a length of less than 10 mm and store it in a clean bottle for later use.
[0070] 3. Weigh 0.5g of the above short fibers and place them in a 50mL Corning centrifuge tube, moistening it with a small amount of water. Add 4mL HCl, 4mL HNO3 and 8mL HF to the centrifuge tube, seal and shake well. Then place the centrifuge tube on a graphite digestion furnace and heat at 125℃ for 2 hours until the fibers dissolve.
[0071] 4. After the centrifuge tubes have cooled to room temperature, unscrew the caps and evaporate them in an open container at 125°C for 6 hours in a graphite digestion furnace until all the liquid has evaporated. Then remove the centrifuge tubes and let them cool slightly to 50°C. Add 2 mL of HNO3 and continue heating in an open container at 125°C in a graphite digestion furnace until all the liquid has evaporated.
[0072] 5. Remove the centrifuge tube and let it cool slightly to 50°C. Rinse the inner wall of the centrifuge tube with a small amount of water, then add 2.5 mL of HNO3 and 15 mL of water, seal and shake well. Place the centrifuge tube on a graphite digestion furnace and heat at 125°C for 2 hours until all the salts are dissolved.
[0073] 6. Remove the centrifuge tube and cool it to room temperature. Use a pipette to transfer all the liquid to a 25mL volumetric flask. Rinse the inside of the tube with water and use a pipette to transfer all the rinsing liquid to the volumetric flask as well. Then make up to volume and shake well before use.
[0074] 7. ICP-OES was used to determine and analyze trace elements such as Na, K, Mg, Fe, and Ca in the sample.
[0075] The analytical steps are as follows:
[0076] S1: Dilute the mother liquor obtained by the digestion method in steps 1-6 by 2 times and set aside; the mother liquor is denoted as S, and the mother liquor diluted by 2 times is denoted as S0;
[0077] S2: Prepare a blank sample solution using steps 1-6, and set it aside for later use;
[0078] S3: Prepare a series of standard solutions:
[0079] Take multi-element national standard solution A (No. GBW(E)083901NCS141017), with a concentration of 100 mg / L, and dilute it with water to obtain solution B with a concentration of 10 mg / L and solution C with a concentration of 5 mg / L.
[0080] Take 5 mL of 2% (w / w) HNO3 solution to obtain a 0 mg / L blank standard solution;
[0081] Take 2.5 mL of the mother solution S, dilute it with 2% nitric acid solution to a final volume of 5 mL, and record it as S0;
[0082] Take 2.5 mL of the mother solution S and 0.1 mL of the diluent C, and dilute to 5 mL with 2% nitric acid solution. Record this as S0+0.1 mg / L.
[0083] Take 2.5 mL of the mother solution S and 0.15 mL of the diluent C, and dilute with 2% nitric acid solution to a final volume of 5 mL. Record this as S0 + 0.3 mg / L.
[0084] Take 2.5 mL of the mother solution S and 0.25 mL of the diluent C, and dilute to 5 mL with 2% nitric acid solution. Record this as S0 + 0.5 mg / L.
[0085] Take 2.5 mL of the stock solution S and 0.5 mL of the diluent C, and dilute with 2% nitric acid solution to a final volume of 5 mL. Record this as S0+1 mg / L.
[0086] Take 2.5 mL of the mother solution S and 0.25 mL of the diluent B, and dilute with 2% nitric acid solution to a final volume of 5 mL. Record this as S0+5 mg / L.
[0087] Take 2.5 mL of the mother solution S and 0.5 mL of the diluent B, and dilute with 2% nitric acid solution to a final volume of 5 mL. Record this as S0+10 mg / L.
[0088] S4: Use ICP-OES to measure the spectral intensity of each element sequentially, select appropriate characteristic spectral lines, and establish a standard working curve:
[0089] Select the spectral lines of the element to be analyzed in the instrument software;
[0090] The instrument's operating parameters were determined. In this embodiment, a PerkinElmer Avio 200 inductively coupled plasma atomic emission spectrometer was used. The recommended operating parameters for the instrument are as follows:
[0091]
[0092] Select the standard addition method and enter the spiking concentration (i.e., 0, 0.1 mg / L, 0.3 mg / L, 0.5 mg / L, 1 mg / L, 5 mg / L, 10 mg / L).
[0093] Subsequently, a series of standard solutions, including 2% nitric acid solution, SO, SO+0.1 mg / L, SO+0.3 mg / L, SO+0.5 mg / L, SO+1 mg / L, SO+5 mg / L, and SO+10 mg / L, were analyzed sequentially using ICP-OES. Working curves were obtained comparing signal intensity with element concentration. The x-axis represents the concentration (mg / L) of each metal element in the standard solution series, and the y-axis represents the emission intensity of each element at different concentrations using the plasma emission spectrum. The control software automatically performed univariate linear regression analysis to establish the working curve. The linear correlation coefficient γ of the working curve should not be less than 0.999; otherwise, the cause should be identified and eliminated before a new calibration curve is established.
[0094] S5: Introduce the prepared sample solution and blank sample solution into ICP-OES, respectively, and determine the content of relevant elements in the samples according to the standard working curve. Among these, the content of trace elements is determined based on their concentration:
[0095] The standard curve points for K and Mg were selected at S0, S0+0.1 mg / L, S0+0.3 mg / L, and S0+0.5 mg / L.
[0096] The standard curve points for Ca were selected at S0, S0+0.5 mg / L, S0+1 mg / L, and S0+5 mg / L.
[0097] The standard curve points for Fe were selected at S0, S0+0.5mg / L, S0+1mg / L, and S0+5mg / L.
[0098] The standard curve points for Na are selected at S0, S0+1 mg / L, S0+5 mg / L, and S0+10 mg / L. Because the content of Na is relatively high, axial observation will cause the measurement results to exceed the instrument's detection range. Therefore, the observation method for this element can be changed to radial.
[0099] Five parallel samples and one blank sample were prepared using the same steps for digestion and determination. The five sample solutions were measured independently, and the average value was taken.
[0100] The measurement data are shown in Table 1. The coefficient of variation (RSD) is <2.5%.
[0101] Table 1. Results of trace element determination of a certain imported alumina fiber in Example 1.
[0102]
[0103]
[0104] Example 2
[0105] The digestion method of this invention was used to completely digest a certain type of domestically produced alumina fiber (main element Al:Si ratio 80:20) for trace element detection. This experiment measured 5 parallel samples and 1 blank sample. The specific steps are as follows:
[0106] 1) Take 5g of fiber sample and put it into a platinum crucible. Place it in a muffle furnace and heat at 625℃ for 2 hours to completely remove the sizing agent or adhesive from the fiber surface.
[0107] 2) Remove the sample and place it in a desiccator to cool to room temperature. Cut it into short fibers with a length of less than 10 mm and store it in a clean bottle for later use.
[0108] 3) Weigh 0.4g of the above short fibers and place them in a 50mL Corning centrifuge tube, moistening it with a small amount of water. Add 3mL HCl, 3mL HNO3 and 6mL HF to the centrifuge tube, seal and shake well. Then place the centrifuge tube on a graphite digestion furnace and heat at 120℃ for 2 hours until the fibers dissolve.
[0109] 4) After the centrifuge tubes have cooled to room temperature, unscrew the caps and evaporate them in an open container at 120°C for 6 hours on a graphite digestion furnace until all the liquid has evaporated. Then remove the centrifuge tubes and let them cool slightly to 50°C. Add 1 mL of HNO3 and continue heating in an open container at 120°C on a graphite digestion furnace until all the liquid has evaporated. Add another 1 mL of HNO3 and continue heating in an open container at 120°C on a graphite digestion furnace until all the liquid has evaporated.
[0110] 5) Remove the centrifuge tube and let it cool slightly to 50°C. Rinse the inner wall of the centrifuge tube with a small amount of water, then add 2.0 mL of HNO3 and 10 mL of water, seal and shake well. Place the centrifuge tube on a graphite digestion furnace and heat at 120°C for 2 hours until all the salts are dissolved.
[0111] 6) Remove the centrifuge tube and cool it to room temperature. Use a pipette to transfer all the liquid to a 25mL volumetric flask. Rinse the inside of the tube with water and use a pipette to transfer all the rinsing liquid to the volumetric flask as well. Then make up to volume and shake well before use.
[0112] 7) Trace elements such as Na, K, Mg, Fe, and Ca in the sample were analyzed using ICP-OES. The analytical procedures and parameters were the same as in Example 1. Five independent determinations of the sample solution were performed, and the average value was taken.
[0113] Five parallel samples and one blank sample were prepared using the same steps for digestion and determination.
[0114] The measurement data are shown in Table 2. The coefficient of variation (RSD) is less than 2.5%.
[0115] Table 2. Results of trace element determination of a domestically produced alumina fiber in Example 2.
[0116]
[0117] Comparative Example 1
[0118] An existing, unoptimized digestion method was used to digest a certain type of domestically produced alumina fiber (main element Al:Si ratio 80:20) from Example 2, and trace elements in the alumina fiber were detected. This experiment measured 5 parallel samples and 1 blank sample. The specific steps are as follows:
[0119] 1) Take 5g of fiber sample and put it into a platinum crucible. Place it in a muffle furnace and heat at 625℃ for 2 hours to completely remove the sizing agent or adhesive from the fiber surface.
[0120] 2) Remove the sample and place it in a desiccator to cool to room temperature. Cut it into short fibers with a length of less than 10 mm and store it in a clean bottle for later use.
[0121] 3) Weigh 0.1g of the above short fibers and place them in a clean platinum crucible, moistening it with a small amount of water. Add 10mL of HF and 2mL of H2SO4 to the platinum crucible, then place the crucible on a flat plate heater and heat at 120°C until the liquid evaporates to about 2mL. Adjust the temperature of the flat plate heater to 320°C and heat until the white fumes cease to appear. This step is to remove the sulfuric acid. The process takes approximately 10 hours.
[0122] 4) Remove the platinum crucible and let it cool slightly. Rinse the inner wall of the crucible with a small amount of water, then add 2 mL of H2SO4 again and heat at 320°C until all white fumes are emitted. This process takes about 5 hours.
[0123] 5) Remove the platinum crucible and let it cool slightly. Add 4 mL of HNO3 and 10 mL of water, and heat at 120°C for 4 hours until all the salts are dissolved.
[0124] 6) Remove the platinum crucible and cool it to room temperature. Use a pipette to transfer all the liquid to a 100mL volumetric flask. Rinse the inner wall of the tube with water and use a pipette to transfer all the rinsing liquid to the volumetric flask as well. Then make up to volume and shake well before use.
[0125] 7) Trace elements such as Na, K, Mg, Fe, and Ca in the sample were analyzed using ICP-OES. The standard addition method was selected for determination. Due to the different element contents in the fibers, the determination stock solution from step 6 was diluted 5 times again before being used to determine the Na content. K, Ca, Fe, and Mg could be directly determined using the determination stock solution from step 6.
[0126] Using the national standard solution of sodium (No.: GBW(E)082159) and the stock solution for determination, prepare standard solutions of sodium element S0, S0+1mg / L, S0+2mg / L, and S0+5mg / L. Establish a working curve for the standard solution of sodium element, and set the standard curve points for sodium element determination as S0, S0+1mg / L, S0+2mg / L, and S0+5mg / L.
[0127] Using the multi-element national standard solution (No.: GBW(E)083901NCS141017) and the stock solution for determination, prepare standard solutions of other elements at concentrations of S0, S0+0.2 mg / L, S0+0.5 mg / L, S0+1 mg / L, S0+3 mg / L, and S0+5 mg / L to establish a standard solution working curve. The standard curve points for K and Mg are selected at S0, S0+0.2 mg / L, S0+0.5 mg / L, and S0+1 mg / L; for Ca, S0, S0+0.5 mg / L, S0+1 mg / L, and S0+3 mg / L; and for Fe, S0, S0+1 mg / L, S0+3 mg / L, and S0+5 mg / L.
[0128] Five parallel samples and one blank sample were prepared using the same steps for digestion and determination.
[0129] The measured data are shown in Table 3. The coefficient of variation (RSD) is between 2% and 13%.
[0130] Table 3. Results of trace element determination of a certain domestic alumina fiber (Comparative Example 1)
[0131]
[0132] Figure 1 This is a comparison chart of the trace element content determination values of Example 2 and Comparative Example 1 of the present invention; Figure 2 The following are the RSD values for trace element determination in Example 2 and Comparative Example 1 of this invention; as shown in Tables 2 and 3. Figure 1 and Figure 2 It can be seen that the measured values of each element increased significantly after the digestion method was optimized, proving that the digestion process was more thorough. The relative standard deviation was significantly reduced after the digestion method was optimized, with the RSD value decreasing from 2%-13% to about 2%, the dispersion decreased, and the repeatability significantly improved.
[0133] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in the present invention should be included within the scope of protection of the present invention.
Claims
1. A digestion method for accurate analysis of trace element content in alumina fibers, characterized in that, The alumina fiber has a main element Al:Si ratio of 72:28 or 80:20, and includes the following steps: Step 1: Place the alumina fiber sample in a platinum crucible, place it in a muffle furnace, and heat it at 620-680℃ for 1-2 hours; Step 2: Remove the alumina fiber sample and place it in a desiccator to cool to room temperature for later use; Step 3: Weigh 0.4-0.5g of alumina fiber sample, put it into a centrifuge tube, moisten it with a small amount of water, add HCl, HNO3 and HF to the centrifuge tube, seal and shake well, place the centrifuge tube on a graphite digestion furnace and heat at a low temperature until the fiber dissolves. The heating temperature is 110-130℃ and the heating time is 1-3h. The mass-to-volume ratio of alumina fiber sample, HCl, HNO3, and HF was 0.4–0.5 g : 3–4 mL : 3–4 mL : 6–8 mL; Step 4: After the centrifuge tube has cooled to room temperature, unscrew the cap of the centrifuge tube and evaporate it in an open container at 110-130°C on a graphite digestion furnace until all the liquid has evaporated. Remove the centrifuge tube and let it cool slightly to 40-60°C. Add 1-2 mL of HNO3 and continue to evaporate it in an open container at 110-130°C on a graphite digestion furnace until all the liquid has evaporated. The step of adding HNO3 and evaporating it in an open container until all the liquid has evaporated is repeated 1-2 times; Step 5: Remove the centrifuge tube and let it cool slightly to 40-60°C. Rinse the inner wall of the centrifuge tube with a small amount of water, add 2-4 mL of HNO3 and 10-15 mL of water, seal and shake well. Place the centrifuge tube on a graphite digestion furnace and heat at 110-130°C for 1.5-2.5 hours until the salts are completely dissolved. Step 6: Remove the centrifuge tube and cool it to room temperature. Transfer all the liquid to a volumetric flask, rinse the inner wall of the tube with water, and transfer all the rinsing liquid to the volumetric flask as well. Make up to volume and shake well. Analyze the elements in the sample using ICP-OES.
2. The digestion method according to claim 1, characterized in that, In step 6, the sample in the centrifuge tube is transferred to a 25 mL volumetric flask, brought to a final volume, and shaken well. ICP-OES is used to analyze five elements in the sample: Na, K, Mg, Fe, and Ca. The relative standard deviation of the measurement results is <2.5%.
3. The digestion method according to claim 1, characterized in that, In step 3, the aperture of the graphite digestion furnace and the diameter of the centrifuge tube are the same.
4. A method for accurately determining the trace element content of alumina fibers, characterized in that, The alumina fiber sample is digested using the digestion method according to any one of claims 1-3, and the determination method includes the following steps: S1. The alumina fiber sample is digested by the digestion method described above. After digestion, the sample is transferred to a volumetric flask, diluted and shaken to obtain the stock solution for testing. S2. Prepare a blank sample solution according to the digestion method described above; S3. Prepare a series of standard solutions; S4. Use ICP-OES to measure the spectral intensity of each element in sequence, select appropriate characteristic spectral lines, and establish a standard working curve; S5. Use ICP-OES to determine the spectral intensity of relevant elements in the sample solution, and calculate the content of relevant elements in the sample according to the standard working curve.